Synthesis and characterization of Sophora alopecuroides L. green synthesized of Ag nanoparticles for the antioxidant, antimicrobial and DNA damage prevention activity - Hamdullah Seçkin; Ismet Meydan (Universidade de São Paulo, 2022)
Abstract In this study, it was aimed to investigate the amount of antioxidant, protective properties against DNA damage and antibacterial properties against various pathogens after the interaction of Ag metal (Ag NPs/Sa) of Sophora alopecuroides L. (S. alopecuroides L) plant seed, which is grown in Iğdır and used in the treatment of many diseases. The DPPH radical quenching activity of Ag NPs/Sa was performed by using Blois method, DNA damage prevention activity by gel electrophoresis and antibacterial property by disk diffusion method. With the green synthesis method, AgNPs obtained as a result of the reaction of the plant and Ag metal are UV visible spectrophotometer (UV-vis), fourier-transformed infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and scanning electron microscope (SEM). DPPH radical quenching activity of Ag NPs/Sa was investigated in the concentration range of 25-250 μg/ml. The radical quenching activity at a concentration of 250 μg/ml was 85,215 ± 0,101%, while this value was 93,018% for the positive control BHA. It has been observed that the protective property of pBR322 plasmid DNA damage against OH radicals originating from H2O2 increases with concentration. It has been observed that Ag NPs/Sa has significant antimicrobial properties against some pathogens (B. subtilis ATCC 6633 E. coli ATCC 25952, B. cereus ATCC 10876, P. aeruginosa ATCC 27853, E. faecalis ATCC 29212, S. aureus ATTC 29213 and C. albicans ATTC 90028) that cause disease and even some pathogens are more effective than antibiotics.